IMPROVEMENTS IN DIAGNOSTICS AND THERAPEUTIC CAPABILITIES OF ENDOVIDEOLAPAROSCOPY FOR COMBINED ABDOMINAL TRAUMA - Umedov Xushvaqt Alisherovich (Research Focus International Scientific Journal, 2024)
Severe combined abdominal trauma is a particular type of injury and one of the leading causes of death among the wounded and injured in both peace and war. Abdominal injuries are directly responsible for 30% of fatalities reported annually due to motor vehicle accidents and have a significant impact on the outcome in an additional 58% of accidents. Abdominal trauma, as a rule, is accompanied by significant dysfunction of the vital organs of the abdominal cavity and retroperitoneal space, which subsequently cause metabolic disorders and the activity of other organs and systems. Most patients with severe combined abdominal trauma can be saved with a quick diagnosis (peritonitis and hemoperitonium), as well as modern active surgical tactics.